The optimal control models of interurban bus transport - Medvedev, Nikolai; Oleschenko, Lubov (My University, 2014)
The models for calculating the number of buses of different types depending on the variable passenger time and a specified interval of vehicles, minimizing the expenses of motor company which is considered to be optimal for the carrier and the passenger range of buses on the route. The influence of the speed of vehicles on the total costs of MTE is analyzed. The proposed model can be used to make effective management decisions regarding the organization of the rolling stock for enterprises passenger transport.
Keywords: оптимізація; витрати; математичне програмування; оптимизация; математическое программирование; издержки; optimization; cost; mathematical programming; кафедра вищої математики імені проф. Можара В. І.